Competition of Acetone Reduction and Hydrogen Evolution on Pt Single Crystal Electrodes in the Absence and Presence of the Ionic Liquid [C2C1Im][OTf] - Kastenmeier, Maximilian; Franz, Evanie; Waidhas, Fabian; Yang, Tian; Taccardi, Nicola; Wasserscheid, Peter; Brummel, Olaf; Libuda, Jörg (Journal of Physical Chemistry C, 2023)
In heterogeneous catalysis, ionic liquids (ILs) are used as chemical modifiers to control selectivity. In our work, we aim to apply the same concept to electrocatalytic systems. We studied two competing reactions on low index platinum (111), (100), and (110) single crystal electrodes, namely, the hydrogen evolution reaction (HER) and the acetone reduction reaction. We used the IL [C2C1Im][OTf] dissolved in the supporting electrolyte (0.1 M HClO4) as chemical modifier. In our study, we combined cyclic voltammetry (CV), electrochemical infrared reflection absorption spectroscopy (EC-IRRAS), and differential electrochemical mass spectrometry (DEMS). On all three surfaces, the HER is the predominant reaction at potentials below 0.00 VRHE. While Pt(100) and Pt(111) show no or very low activity toward the reduction of acetone, the Pt(110) surface is active for this reaction in a potential window between 0.08 and 0.00 VRHE. We identified propane to be the main product of acetone reduction. Additionally, we observed the formation of adsorbed COads. In the presence of low concentrations of the IL (0.001 M), acetone reduction is fully suppressed and the activity for HER increases. We assign these effects to the specific adsorption of the IL, which blocks the adsorption sites for sterically more demanding acetone, while the coadsorbate layer remains permeable for the sterically less demanding hydrogen formation. Our results illustrate the potential of ionic liquids to act as molecular filters, which block a specific reaction channel.
CRIS-Team Scopus Importer:2023-12-15

C[sbnd]C bond cleavage in the electrooxidation of 2,3-butanediol controlled by an ionic liquid modifier - Yang, Juntao; Haßfurther, Florian; Hilpert, Felix; Hussain, Zarah; Yang, Tian; Taccardi, Nicola; Wasserscheid, Peter; Brummel, Olaf; Libuda, Jörg (Journal of Catalysis, 2024)
In heterogeneous catalysis, ionic liquids (ILs) are used as chemical modifiers to control selectivity. In our work, we aim to apply the same concept to electrocatalytic systems. As a model reaction, we studied the electrooxidation of 2,3-butanediol on the low-index Pt(1 1 1), Pt(1 0 0) and Pt(1 1 0) surfaces in an acidic environment. We used the IL 1-ethyl-3-methylimidazolium trifluoromethanesulfonate ([C2C1Im][OTf]) dissolved in an aqueous electrolyte as a catalyst modifier. The reaction mechanisms were investigated by electrochemical infrared reflection absorption spectroscopy (EC-IRRAS). The oxidation of 2,3-butanediol is highly structure dependent. On all three surfaces, the two products formed are acetoin and diacetyl, i.e. either one or two alcohol functionalities are oxidized. However, we observe distinct features on the different surfaces with respect to activity, potential window of oxidation, and selectivity. Only the Pt(1 0 0) surface is active towards C[sbnd]C bond cleavage. The latter reaction leads to the formation of COads and poisoning of the catalyst. Modification of this surface by addition of the IL leads to an increase of the selectivity for acetoin from 51 % to 78 % (at 1.1 VRHE). In addition, C[sbnd]C bond cleavage is suppressed, no CO is formed, and the surface remains active for the target reaction. We attribute these effects to the reversible and structure dependent adsorption of the [OTf]− anions on the Pt surfaces and additional interionic interactions. Our results demonstrate the potential of ILs to control selectivity in electrocatalytic reactions.
CRIS-Team Scopus Importer:2024-05-31
Keywords: In-situ IR spectroscopy; Ionic liquids; Platinum; Secondary alcohols; Selectivity; Single crystals; Supported catalyst with ionic liquid layer

Electrochemically controlled energy release from a norbornadiene-based solar thermal fuel: increasing the reversibility to 99.8% using HOPG as the electrode material - Waidhas, Fabian; Jevric, Martyn; Bosch, Michael; Yang, Tian; Franz, Evanie; Liu, Zhi; Bachmann, Julien; Moth-Poulsen, Kasper; Brummel, Olaf; Libuda, Jörg (Journal of Materials Chemistry A, 2020)
Solar energy conversion using molecular photoswitches holds great potential to store energy from sunlight in the form of chemical energy in a process that can be easily implemented in a direct solar energy storage device. In this context, we investigated the electrochemically triggered energy release of a solar thermal fuel based on the norbornadiene (NBD)/quadricyclane (QC) couple by photoelectrochemical IR reflection absorption spectroscopy (PEC-IRRAS). We studied the photo-induced conversion of the energy-lean 2-cyano-3-(3,4-dimethoxyphenyl)-norbornadiene (NBD ') to the energy-rich 2-cyano-3-(3,4-dimethoxyphenyl)-quadricyclane (QC ') and the electrochemically triggered reconversion using highly oriented pyrolytic graphite (HOPG) as an electrode material. We compared our results with the results obtained previously using Pt(111) electrodes and we characterized the photochemical and electrochemical properties of the storage system. NBD ' can be photochemically converted and electrochemically reconverted with very high selectivity. HOPG largely suppresses the unwanted catalytic reconversion which was observed on Pt(111). We performed repetitive cycling experiments for 1000 cycles to determine the reversibility of the system. Our results show that it is possible to reach reversibility above 99.8% using HOPG as an electrode material.
CRIS-Team WoS Importer:2020-09-04

Modifying the Electrocatalytic Selectivity of Oxidation Reactions with Ionic Liquids - Yang, Tian; Yang, Juntao; Deng, Xin; Franz, Evanie; Fromm, Lukas; Taccardi, Nicola; Liu, Zhi; Görling, Andreas; Wasserscheid, Peter; Brummel, Olaf; Libuda, Jörg (Angewandte Chemie International Edition, 2022)
The "solid catalyst with ionic liquid layer" (SCILL) is an extremely successful new concept in heterogeneous catalysis. The idea is to boost the selectivity of a catalyst by its modification with an ionic liquid (IL). Here, we show that it is possible to use the same concept in electrocatalysis for the selective transformation of organic compounds. We scrutinize the electrooxidation of 2,3-butanediol, a reaction which yields two products, singly oxidized acetoin and doubly oxidized diacetyl. When adding the IL (1-ethyl-3-methyl-imidazolium trifluormethanesulfonate, [C(2)C(1)Im][OTf]), the selectivity for acetoin increases drastically. By in situ spectroscopy, we analyze the underlying mechanism: Specific adsorption of the IL anions suppresses the activation of water for the second oxidation step and, thus, enhances the selectivity for acetoin. Our study demonstrates the great potential of this approach for selective transformation of organic compounds.
CRIS-Team WoS Importer:2022-06-03